LOWERING CHOLESTEROL WITH HIIT: AN EFFECTIVE SOLUTION FOR OVERWEIGHT WOMEN - Vigriawan, Gosy Endra; Raharjo, Slamet; Andiana, Olivia; Yunus, Mahmud; Pribadi, Heri Purnama; Abdullah, Ahmad; Sugiarto, Dinta; Yuniarto, Andryas; Kusuma Bakti, Fajar Raya Ferdinal; Ayubi, Novadri; Airlangga Daulay, Dio Alif (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
A sedentary lifestyle is a major risk factor for cardiovascular disease, especially in women who are overweight. High-Intensity Interval Training (HIIT) has been known as an effective exercise method in improving cardiometabolic health. This study aims to analyze the effect of HIIT on total cholesterol levels in overweight women with a sedentary lifestyle. The research method used an experimental design with two groups, namely the treatment group that underwent a HIIT program for several weeks and the control group that did not undergo exercise. The results showed that there was a significant difference in changes in total cholesterol levels between the treatment group and the control group, where the group that did HIIT experienced a greater decrease in cholesterol levels. These findings support that HIIT has the potential to be an effective intervention to lower total cholesterol levels in populations at risk of cardiovascular disorders. HIIT can be a practical and efficient alternative for individuals with limited time to manage their heart and metabolic health.